Mapping the Global Research on Environmental, Social, Governance (ESG): A Bibliometric Analysis - Lowar, Dhan Bahadur; Devkota, Niranjan; Siddique, Majibur Rahman (NCC Journal, 2025)
In the contemporary business landscape, firm evaluation increasingly extends beyond traditional financial indicators to encompass environmental sustainability, social responsibility, and governance practices. Environmental, Social, and Governance (ESG) factors have emerged as fundamental drivers of corporate values and sustainable financial performance, introduced through the UN Global Compact initiative’s Who Cares Wins report, and are now considered central to global corporate strategies, shaping accountability, transparency, and ethical business conduct. This study conducts a comprehensive bibliometric analysis to map the global ESG research landscape, examining the current state of knowledge, key trends, and future directions. Data were extracted from the Scopus database, comprising 3,177 articles published between 2008 and 2026, and analyzed using VOSviewer and Biblioshiny (R). The performance analysis evaluated annual scientific production, leading sources, authors, affiliations, countries, and most cited documents, while science mapping examined keyword occurrence, word clouds, co-authorship networks, thematic mapping, and thematic evolution. Results indicate that annual scientific production peaked in 2025 with 1,305 publications, with Sustainability emerging as the most influential journal. China (1,629 publications) and the USA (605 publications) led in productivity, while China (15,062 citations) and the USA (10,035 citations) dominated in citation impact. Keyword analysis identified “ESG,” “Sustainability,” and “Responsible Investment” as the most prominent themes. Overall, this study provides a structured overview of global ESG research, identifies influential contributors and sources, and highlights emerging thematic areas, offering a roadmap for scholars, practitioners, and policymakers aiming to advance ESG-focused research and implementation worldwide.